Ultrasound Technique Based on Liposome Nanovesicles in the Evaluation of Abnormal Pregnancy Outcomes in Diabetic Women - Wang, Jun; Sun, Xiaojie; Wang, Wenjuan; Zhao, Xinyan; Zhou, Fengyi; Liu, Hui; Li, Liyun (Cellular and Molecular Biology, 2022)
Gestational diabetes mellitus (GDM) refers to the first occurrence or detection of glucose tolerance abnormalities during pregnancy, including cases that may have existed before pregnancy but have not been detected. It is one of the common complications during pregnancy. In recent years, the incidence of GDM is on the rise. The most common complication of GDM is macrosomia, which often causes dystocia, neonatal asphyxia, birth injury and postpartum bleached blood. Early diagnosis, appropriate treatment and maintenance of reasonable and stable blood glucose concentration can significantly reduce the incidence of complications. The purpose of this study was to investigate the application of ultrasound technique based on liposome nano-vesicles in the assessment of abnormal pregnancy outcomes in diabetic pregnant women. Objective: To investigate the value of ultrasound in the examination of fetal growth in pregnant women with gestational diabetes mellitus. Methods a total of 100 pregnant women with gestational diabetes admitted to the hospital were selected as the research objects, and the clinical data of ultrasound examination were retrospectively analyzed. According to the newborn weight, they were divided into control group (normal fetus group) and observation group (giant fetus group). The growth of fetuses in the two groups was compared, and the predictive value of each measurement index to the weight of giant fetus was analyzed.Multiple regression analysis showed that LL, AC and FL played a decisive role in fetal weight, with statistically significant differences (P<0.05). Conclusion Ultrasonography is of great value in predicting fetal growth in pregnant women with gestational diabetes mellitus and can be widely used.